The Effect of Purple Sweet Potato Flour Substitution (Ipomoea Potato L. Poir) On Physical Quality and Sensory Quality of Chiffon Cake - Nailah Ghaisani Alyani; Guspri Devi Artanti; Mariani Mariani (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study aims to analyze the effect of purple sweet potato flour substitution on the physical and sensory quality of chiffon cake. This study was conducted at the Pastry and Bakery Laboratory of the Culinary Arts Education Study Program, Jakarta State University. The study period began in October 2024 and ended in September 2025. The method used in this study was an experimental method. The research sample was a chiffon cake with purple sweet potato flour substitution of 30%, 45%, and 60%. The results of the physical quality test using the ANOVA test showed no significant effect on baked loss. The results of the Duncan test showed that 60% substitution was the product with the best rise power and 45% substitution was the product with the best rise power stability. Sensory quality assessment was carried out on 45 semi-trained panelists who assessed the aspects of crust color, crumb color, aroma, sweetness, purple sweet potato flavor, texture, and pores. The results of the statistical hypothesis of sensory quality with the Kruskal-Wallis test showed that there was no effect of purple sweet potato flour substitution on sensory quality in the aspects of aroma, sweetness, purple sweet potato flavor, texture, and pores. However, there was a significant effect on sensory quality in the aspects of crust and crumb color. The results of the Tuckey's test showed that the 60% substitution chiffon cake product was the best product, so it can be concluded that the chiffon cake with 60% purple sweet potato flour substitution was the product with the best physical quality and sensory quality. Therefore, to optimize the use of purple sweet potato flour, it is recommended that the 60% substitution chiffon cake product can be further developed..